Facial restoration by transplantation: the Brigham and Women's face transplant experience - Westvik, Tormod S; Dermietzel, Alexander; Pomahač, Bohdan (Annals of plastic surgery, 2015)
Since 2009, the face transplant team at Brigham and Women's Hospital in Boston has performed 6 successful partial and full facial transplantations on carefully selected patients. The development of these techniques has led to a new era in facial reconstruction which now more correctly can be described as facial restoration. Besides the obvious facts of giving someone with a missing or severely disfigured face a new appearance, facial restoration has led to many other interesting observations in terms of immunologic models, airway functionality, sensory recovery and cerebral cortical functioning. In this article, we present an overview of our experience, and where we are today-also presenting some of the interesting avenues that have opened and will lead us further in the daunting experience of facial allotransplantation.